LEGAL STUDY OF ABUSE OF OFFICE LEADING TO CRIMINAL ACT OF CORRUPTION IN INDONESIA - Roland Sahat Uli Banjarnahor; Ismaidar; T. Riza Zarzani (Journal of International Islamic Law, Human Right and Public Policy, 2024)
One of the things that hinders the country's economic growth is corruption. Any illegal activity directed at the country's economy or finances needs to be stopped and handled fairly. Abuse of authority, trust, or public or state office for personal gain is the reason that causes corruption. Corruption is classified as an extraordinary crime in order to hinder prosecution because it is difficult to prove the reason for the crime during the trial. those involved in corruption, and those who comply with it. The discussion in this studyHow is the Legal Study of Abuse of Office So That Corruption Occurs? And How is the Regulation of Abuse of Office in Corruption?, then the research method used is the normative legal research method, and the discussion of this study is, as regulated in Law Number 31 of 1999 and Law Number 20 of 2001 concerning the Eradication of Corruption, a legal study of the regulation of abuse of office so that corruption occurs is caused by abuse of authority in office.